SOCIO-EMOTIONAL DEVELOPMENT OF EARLY CHILDREN - Annisa Salsabila (Universitas Pendidikan Indonesia, 2021)
Human development is a complex aspect. Human development has 4 domains, namely physical development, intellectual development, social and emotional development. Social and emotional development in children is indeed a different aspect but cannot be separated. The point is that if we discuss the social aspects of children, it must intersect with the emotional aspects of children. And vice versa, if we study children's emotions, then we must also discuss the social aspects of students. Social development is an increase in a person's ability to interact with others while emotional development is a person's ability to control the emotions that are being experienced by using verbal or nonverbal messages so that they can be known by others. This article discusses the socio-emotional development of children using the literature review method. The researcher found 59 articles from one database, of which 12 were finally obtained